APPLICATIONS OF ROTATIONAL DYNAMICS IN GYROSCOPE-BASED SENSORS: A SYSTEMATIC LITERATURE REVIEW - Putri, Mutiara; Sutanto, Taufiq; Akhsan, Hamdi; Ismet, Ismet (Universitas Nusa Cendana, 2026)
Gyroscope-based sensors measure angular velocity in consumer electronics, robotics, and navigation. However, research lacks explicit relationship between rotational dynamics principles and optimisation of sensor architectures. This review examines the application of mechanical concepts conservation of angular momentum, moment of inertia, torque, and the Coriolis effect to gyroscope-based sensors. Per PRISMA guidelines, twelve studies between 2020 and 2026 were selected from Scopus, ScienceDirect, DOAJ, and IEEE Xplore. The stringent inclusion criteria coupling classical rotational dynamics with architectural optimization, yielding a highly specialized but methodologically rigorous dataset. Study quality was assessed using a standardized critical appraisal checklist. Operational mechanisms, error dynamics, control strategies, and performance optimisation in MEMS, atomic, and photonic systems are the main topics. Three themes emerge from the findings: (1) mechanical flaws are error sources calling for control engineering; (2) mode splitting and bias instability decrease accuracy but can be lessened with control systems and electrostatic tuning; and (3) testing protocols must be standardised because of data from operating environments. Sensor accuracy and stability can be improved by combining rotational dynamics principles with control techniques like Kalman filtering and fuzzy logic, achieving scale-factor stabilization residuals as low as 2 ppm and bias instability reductions exceeding 50% in optimized architectures.